SCHOOL ENTERPRISE: NURTURING STUDENTS’ ENTREPRENEURIAL SKILLS THROUGH SALES BOOTH - Dydimus, Dydinelynn; Masli, Sunarti Nur Amirah; Idek, Sirhajwan (PEOPLE: International Journal of Social Sciences, 2019)
School Enterprise is an approach in learning that aims to foster students’ entrepreneurial skills and enhance their competence in managing business projects. Thus, the Business Management Programme of Keningau Vocational College decided to launch the School Enterprise Project in order to boost the students’ skills in entrepreneurship. The aim of the project was to provide more opportunities for students to demonstrate their skills in making sales and profits. The funds raised during this project would be used to purchase reference books on topics related to business management since there was shortage of such books at the college. An intact class of 14 students were involved in the study and they were assigned into five teams in which each team set up their own booth to sell their merchandises. The data were collected through observation, survey and an analysis of their business plan including their profits. The findings showed that the result were positive as students gained profits from sales that they successfully made and they displayed optimistic views on their experience. It was recommended that this project should be turned into a regular assignment.